Cross-cultural Comparison of Medicinal Plants Used to Treat Infections in Northern Thailand - Kamonnate Srithi (2019)
© 2019, The New York Botanical Garden. Drug resistance in pathogenic microorganisms threatens both human and animal health. This has prompted the search for new antimicrobial drugs, including the ones from plant-derived medicines. Some researchers have suggested that medicinal plants used by multiple cultures are more likely to be pharmacologically active. We interviewed 808 informants across seven ethnic groups in northern Thailand about their traditional knowledge of medicinal plants. Plants used to treat infections were compared and agreement about a particular use of a plant was evaluated using the “frequency of citation.” When agreements were found between two or more informants, we searched for confirmation in other studies for medicinal uses and biological activities reported for that particular plant species. Of the 808 informants, 103 mentioned 199 distinct plant uses of 143 plant species to treat 21 different “infection” disorders. Of the 199 plant uses, 114 were mentioned by two or more informants; 15 plant uses were shared between different ethnic groups and 55 plant uses were shared within the same ethnic group and had identical or similar uses mentioned in other studies, sometimes in distantly located cultures. The convergent information suggests the bioactivity of a certain plant that may have been discovered independently. However, the remaining 44 plant uses that were shared within the same ethnic group are here reported for the first time with considerable agreement among informants. These new plant uses should be given high priority in bioscreening for new antimicrobial drugs.